Kajian Hukum Mengenai Tindakan Korps Brigade Mobil Polri Terhadap Pelaku Pelanggaran Protokol Kesehatan Covid-19 - Damai Syukur Waruwu; Ediwarman Ediwarman; Marlina Marlina (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This paper aims to examine and analyze the legal rules governing the perpetrators of the Covid-19 health protocol violation, the factors causing the Covid-19 health protocol violation in North Sumatra, and the policies taken by the Police Mobile Brigade Corps against the Covid-19 health protocol violations. . The problem is that the Covid-19 pandemic demands a response from the Police as law enforcement officers in playing their role in disease control efforts, educating the public, and taking action against crimes that see the outbreak as an opportunity to commit various crimes. To approach this problem, the theory of the legal system is used. The data were collected through interview guidelines and analyzed qualitatively. This study concludes that the legal rules governing the perpetrators of violating the Covid-19 health protocol are regulated in Law Number 2 of 2002 concerning the Indonesian National Police, Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions (PSBB) in the Context of Accelerating Handling Corona Virus Disease 2019 (Covid-19), as well as other regulations such as Telegram Letter Numbered ST/3220/XI/KES.7./2020, Regulation of the Minister of Health, Instruction of the Minister of Home Affairs. Factors that encourage violations of health protocols are internal factors consisting of economic factors and lack of public concern. External factors consist of people's habits, people's distrust of the government, the existence of new normal policies. Brimob policies taken are penal and non-penal policies.